2011
DOI: 10.1080/10934529.2011.609458
|View full text |Cite
|
Sign up to set email alerts
|

Electro-osmotic fluxes in multi-well electro-remediation processes

Abstract: In recent years, electrokinetic techniques on a laboratory scale have been studied but few applications have been assessed at full-scale. In this work, a mock-up plant with two rows of three electrodes positioned in semipermeable electrolyte wells has been used to study the electro-osmotic flux distribution. Water accumulated in the cathodic wells when an electric voltage gradient was applied between the two electrode-well rows. Likewise, slight differences in the water flux were observed depending on the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…The polarity reversal strategy applied in this study causes reversal in the EOF direction, and it has been reported that it also results in a lower volume of water being transported to the electrode wells [22]. This is an important aspect from a biological perspective because it would improve the distribution of the nutrients and reduce the nutrients removed from the soil, thus allowing better performance of the pollutant's biodegradation process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…The polarity reversal strategy applied in this study causes reversal in the EOF direction, and it has been reported that it also results in a lower volume of water being transported to the electrode wells [22]. This is an important aspect from a biological perspective because it would improve the distribution of the nutrients and reduce the nutrients removed from the soil, thus allowing better performance of the pollutant's biodegradation process [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…One very important parameter in the EKSF processes is the pH, which is also directly related to intensity of the electric current. The pH is known to change in a different fashion (Lopez-Vizcaino et al, 2011) in both the anode and the cathode, as shown in Figure 5. without any EKSF remediation process after this spill.…”
Section: Methodsmentioning
confidence: 99%
“…This material is not reactive and it has a low hydraulic conductivity, low cation exchange capacity and zero organic content [36][37][38]. The atrazine was selected as a model organic compound and it was obtained from Fluka.…”
Section: Methodsmentioning
confidence: 99%